2021
DOI: 10.1177/2050313x20952224
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Manual therapies promote resolution of persistent post-concussion symptoms in a 24-year-old athlete

Abstract: This case report illustrates the treatment outcomes of a collegiate athlete presenting with an 18-month history of post-concussion syndrome who received a series of mixed manual therapies in isolation of other therapy. Persistent symptoms were self-reported as debilitating, contributing to self-removal from participation in school, work, and leisure activities. Patient and parent interviews captured the history of multiple concussions and other sports-related injuries. Neurological screening and activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 68 publications
(112 reference statements)
0
0
0
Order By: Relevance
“…A total of 317 potential articles were extracted from the database search via electronic media. Undergoing the PRISMA screening and eligibility procedure, only 7 articles were included in the qualitative synthesis [16,19,30,31,32,33] The details of the study selection are shown in Figure 1. Out of 7 articles, there were 2 case series [16,33], 4 case studies/reports [19,20,31,32], and only 1 pilot study [30].…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 317 potential articles were extracted from the database search via electronic media. Undergoing the PRISMA screening and eligibility procedure, only 7 articles were included in the qualitative synthesis [16,19,30,31,32,33] The details of the study selection are shown in Figure 1. Out of 7 articles, there were 2 case series [16,33], 4 case studies/reports [19,20,31,32], and only 1 pilot study [30].…”
Section: Study Selectionmentioning
confidence: 99%
“…Of 7 studies, 4 included athletic participants [16,19,31,33], and the remaining 3 included non-athletic people [20,30,32]. The total number of participants included in the study was 32, of which 28 were males and 4 were females, from varied age groups ranging from 20 to 70 years.…”
Section: Participant's Characteristics Of the Studies Includedmentioning
confidence: 99%
See 3 more Smart Citations